Synthesis and Characterization of a Stable Copper(I) Complex for Radiopharmaceutical Applications. Issue 9 (24th June 2014) - Bodio, Ewen; Boujtita, Mohammed; Julienne, Karine; Le Saec, Patricia; Gouin, Sébastien G.; Hamon, Jonathan; Renault, Eric; Deniaud, David
Abstract A highly stable copper(I) complex was obtained starting from a copper(II) salt. This compound was characterized by a combination of several analytical techniques (UV/Vis spectroscopy, energy‐dispersive X‐ray spectroscopy, electrochemistry, and X‐ray photoelectron spectroscopy) and was shown to present an N4Cu structure. These results were confirmed by a density functional calculations study of the binding energy and the electronic structure of model ligand and copper complexes. Preliminary tests of complexation showed a high ability of the corresponding ligand to chelate 64Cu in very diluted medium, which is of interest for developing new positron emission tomography imaging agents. The stability and the kinetic inertness of the complex are promising. In particular, it displayed good redox stability, which is important because in vivo reduction or oxidation of the copper of Cu complexes can lead to demetalation. The rapid microwave‐assisted strategy used to synthesize the ligand was applied to the synthesis of more than ten ligands. One of these was functionalized by an amino group to form a bifunctional chelate for a future bioconjugation for applications in nuclear medicine.